How playable advertisements affect Gen Z’s intention to download apps in Ho Chi Minh City - Long Cuu Hoang; Hoan Phuc Ho; Hung Xuan Dao; Binh Gia Nguyen; Giang Vu Chau Le; Ha Nhu Ngoc Nguyen (Ho Chi Minh City Open University Journal of Science - Economics and Business Administration)
With the rapid growth of the Internet and portable devices such as smartphones and tablets, mobile advertisements have become a powerful, widely implemented marketing method. Having been popularly developed from 2014 - 2015, playable advertisements quickly gained intentions from advertisers, marketers, and app creators. However, due to the novelty of this advertising method, its effect on Gen Z audiences’ app-downloading intention in Ho Chi Minh City has not been examined yet. Therefore, this study aims to make further investigations into this topic by using the Theory of Reasoned Action (TRA), the Use and Gratification Theory (UGT) and the Theory of Planned Behavior (TPB). The research is conducted with a sample size of 342 respondents, and an online questionnaire is used to collect data from these research participants. The collected data is analyzed using Partial-Least-Squares Structural Equation Modeling (PLS-SEM), which subsequently indicates that these audiences’ attitudes, which are directly affected by their perceived value of the advertisements, are significantly associated with their intentions to download the advertised apps. Particularly, the respondents’ perceived value tends to be positively enhanced, which then stimulates an increase in their attitude towards the advertisements and consequently boosts their app-downloading intention once the credibility and entertainment of that advertisement are high, while the irritation is at a reasonably low level. A mediating effect of these Gen Z audiences’ attitudes in the relationship between advertising value and their app-downloading intentions is also found in this research. Overall, findings from this research are able to provide further understanding of which criteria affect the experience, perspectives, and responses of Gen Z audiences in Ho Chi Minh City when they interact with playable advertisements, which is insightful for advertisers, marketers, and app creators in applying the right advertising method into their mobile marketing strategies.